(untitled) (Research, Society and Development, 2021)
The pharmacological treatment of obesity is constantly updated and the development of new products and proposals is often seen as a controversial option that requires a careful evaluation for its use, both with regard to the patient’s clinical condition and the general characteristics of the drug. to be used, making it necessary to know about its action and safety profiles related to its use. The objective is identify and systematize the most recent data present in the literature on the main drugs used in the treatment of obesity in Brazil and their adverse reactions. Integrative review of articles published in Portuguese, English and Spanish, available in full on LILACS, BIREME (BVS) and MedLine databases. The keywords "drug therapy" AND "obesity" were used for the LILACS database, "pharmacological therapy" AND "obesity" for the Medline / Pubmed database and "drugs" AND "anti-obesity" for the BIREME / VHL database for articles published in the period from 2015 to 2020, 15 studies were selected and analyzed. Results: in LILACs, MEDLINE / PUBMED and BIREME / VHL databases, 16, 49 and 305 articles were obtained, respectively, as results. At the end of all analyzes and selection criteria, 15 articles were included in the present study. Most of the drugs approved for the pharmacotherapy of obesity in Brazil have demonstrated in clinical trials well-established efficacy in weight loss. Similar rates of adverse events were observed between orlistat, liraglutide and lorcaserin, with liraglutide having the largest gastrointestinal events in the group. In the study carried out, the possibilities of new pharmacological treatments for obesity that showed greater strength in the results of weight loss, were exenatide and melatonin, with efficacy demonstrated in clinical trials.